Hydro-abrasive erosion in Kaplan turbines: a case study - Arora, Naman; Kumar, Arun; Singal, Sunil Kumar (Journal of hydroinformatics, 2024)
Sediment in the flowing water causes hydro-abrasive erosion of hydraulic turbines and other underwater components. In the present study, erosion quantification in the Kaplan turbine of a low-head hydropower plant (HPP) on the Upper Ganga Canal, is considered in the study. The study uses the guidelines of the International Electrotechnical Commission IEC 62364: 2019 for quantifying erosion in the Kaplan turbine. This work extends the research of Rai and Kumar (2016) and uses their primary details of some suspended sediment and operating parameters. The shape and mineral composition of the suspended sediment were quantified using dynamic imaging and X-ray diffraction techniques, respectively. The annual average particle load at the study HPP is obtained to be 356.87 kg·h/m3. Based on the analysis, it is estimated that the erosion depth varies from 0.88 to 1.37 mm/year at the blade tip, whereas from 2.40 to 3.74 mm/year at the blade outlet. At the runner chamber, the erosion depth varies from 1.27 to 1.98 mm/year. The erosion depth varies from 0.01 to 1.53 mm/year in the guide vanes. The calibration factor corresponding to the maximum erosion in guide vanes is estimated to be 1.75 × 10−5.